Upaya Peningkatan Pengetahuan Pada Remaja Tentang Dampak Pernikahan Dini Bagi Kesehatan - Ruri Yuni Astari Ruri; Yeni Paramitha (Yayasan Riset dan Pengembangan Intelektual, 2021)
Early marriage has had a profound impact on adolescents and has become a barrier to individual and social development. Some strategies that can be done are providing health education to adolescents. The purpose of this activity is to increase knowledge for adolescents about the impact of early marriage. This activity involved 30 teenagers aged 13-19 years old in Ciborelang Village, Jatiwangi Majalengka Subdistrict, so that they have good knowledge of the impact of early marriage. The method used is counseling using PPT media and video. The results of this service show that adolescents have good knowledge, give positive responses and are very enthusiastic in this outreach activity. Keywords: Knowledge, youth, early marriage